Peta Elektronik Sebagai Media Informasi Bagi Tunanetra Berbasis Labview dan NI MyRio-1900 - Zulfatman; Akhyar Anadiansyah; Nurkasan (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
Electronic map is one of the learning media developed for the blind. The media can fulfill the blind needs in acquiring knowledge. This study aims to develop electronic map as learning media for the blind. On this electronic map, the TCS3200 color sensor was used to recognize embossed maps that have been given different colors. Each color had different RGB frequencies and values. NI MyRio-1900 served as an interface that integrated personal computer as a human machine interface with sensors. Through NI MyRio-1900, personal computer can find out the responses generated by the sensor in matching colors, acquire the period, duty cycle, total frequency, and frequency graph, and can sort the information to be conveyed to the blind. Information about the area whose color was read by the sensor would be delivered through a loudspeaker. From the tests performed, it appeared that the TCS3200 color sensor was able to detect 28 color areas on the map correctly, with RGB sensor values were slightly different from the RGB values in the literature. Malang, for example, was light green, had a frequency value of each R = 345, G = 226, and B = 117, which was converted to obtain the RGB sensor value of R = 140, G = 194, B = 64, with period value of 0.00001715 s, 52.2145% duty cycle, and voice issued in the form of information and potential in the area of Malang.